Analisis Sistem Pengumpulan dan Pencatatan Donasi pada Program Jumat Berkah dalam Perspektif Akuntansi Syariah: (Studi Kasus Wahdah Inspirasi Zakat Kabupaten Bone) - Nanda Darista; Musrini Muis; Hartas Hasbi (AKUNTANSI 45, 2026)
This study aims to analyze the mechanism of collecting and recording donations in the Friday Blessings Program managed by Wahdah Inspirasi Zakat (WIZ) Bone Regency from a sharia accounting perspective. The program is a form of Islamic philanthropy that collects public funds in cash and non-cash forms to be distributed to beneficiaries, with the treatment being tied to infaq because its use is directed to specific activities. This study uses a qualitative approach through a case study method with data collection techniques including in-depth interviews, observation, and documentation. The research findings indicate that the fundraising process has been carried out through various media, such as direct receipts, bank transfers, and in-kind donations, while financial recording remains simple and cash flow-oriented, despite being equipped with verification procedures and limited use of digital technology. In addition, the practice of recording and presenting financial reports has not fully aligned with applicable regulations. Reviewed from the principles of sharia accounting, fund management has reflected the values of trust, transparency, accountability, and fairness, although there are still weaknesses in the presentation of non-cash donations and the systematic preparation of financial reports. Therefore, efforts are needed to improve the quality of financial management to be more in line with sharia accounting standards.